MSME technology adaptation strategy in the city of Salatiga during the covid-19 pandemic - Fikri Fatoni; Yozi Aulia Rahman (Universitas Negeri Semarang, 2024)
Strategy is the planning and execution of an activity within a certain time to achieve a goal effectively. The purpose of this research is to describe and identify the profile of MSMEs in Salatiga City that are affected by the Covid-19 pandemic The type of research used in this research is quantitative research. The method used in this research is descriptive statistical analysis method and AHP (Analitycal Hierarchy Process) method with a total of 40 respondents and 5 key respondents. The results show that the profile of MSMEs affected by the Covid-19 pandemic is that most business actors have more than 2 employees. The impact of the technology adaptation strategy on MSMEs in Salatiga City on the economic conditions of business actors is shown through income stability during the COVID-19 pandemic. The social condition of the community is also affected from work status to how to transact. Based on the results of the AHP analysis, the most prioritized policies for MSME actors are realizing community empowerment, especially MSME actors in Salatiga City through education, training, and economic activities. With the technology adaptation strategy for MSME actors, it can help in maintaining business during the Covid-19 pandemic.